1992
DOI: 10.1302/0301-620x.74b5.1527115
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis of congenital dislocation of the hip

Abstract: In this prospective study, 35,550 neonates were examined shortly after birth by a team of orthopaedic surgeons. They diagnosed 775 unstable or dislocated hips in 656 babies; there were two teratological dislocations. Treatment was first with a Frejka pillow and, if this failed to give a normal hip, a Pavlik harness at three months. Early clinical examination did not identify 21 infants who were found to have subluxation or dislocation of the hip at the three-month review. The number of missed cases declined du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…Most authors have recommended treatment from birth for all newborn infants with NHI because this is a simple practical policy for routine clinical work. [1][2][3][4][5][6][7][8] Treatment can lead to serious complications such as avascular necrosis of the femoral head and the number of infants so managed should therefore be kept as low as possible. Over-treatment can be reduced by improved diagnostic techniques and delaying the decision to initiate it.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most authors have recommended treatment from birth for all newborn infants with NHI because this is a simple practical policy for routine clinical work. [1][2][3][4][5][6][7][8] Treatment can lead to serious complications such as avascular necrosis of the femoral head and the number of infants so managed should therefore be kept as low as possible. Over-treatment can be reduced by improved diagnostic techniques and delaying the decision to initiate it.…”
Section: Resultsmentioning
confidence: 99%
“…6,22,23 Hips with mild instability have been called 'slidey', 'lax' or 'unstable'. 8,24,25 These complex and rather confusing classifications reflect the spectrum of severity of unstable hips and the subjective nature of clinical evaluation. Our classification was also based on clinical evaluation by experienced examiners and was chosen for two reasons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher rate of avascular necrosis is found in older patients, and often the treatment is more invasive, which supports earlier screening for and identification of developmental dysplasia of the hip 38 . In several studies, screening with clinical examination alone has been found to reduce the rate of, but not to eliminate, late-presenting developmental dysplasia of the hip 39,61,[66][67][68][69] . The United States Preventive Services Task Force consensus finding that they were ''unable to assess the balance of benefits and harms of screening'' for developmental dysplasia of the hip 6 speaks to the complexity of the problem and a large amount of data as well as the lack of natural history comparison studies 3 , and this position has been very concerning to some of those who treat this problem 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis enables more effective treatment to be implemented with fewer complications and better results. 7,8 Likewise, the financial cost of treating DDH is also much reduced with early detection and diagnosis.…”
Section: Introductionmentioning
confidence: 99%